The Influences of Economic Diversification and the mediating Effect of Industrial Development on Economic Growth in Oman: A Conceptual Framework - Al Yahyai, Nasr; Azalina, Aza; Supian, Kamisah (Advances in Social Sciences Research Journal, 2020)
Industry is at the heart of a government's plans to transform the economy from a resource-based economy to a value-added one. Economic diversification is vital to countries’ long-term economic growth, but many resource-rich countries remain heavily reliant on revenues generated by natural resources such as mineral or oil production. In Oman, the fall in price oil compelled the government to rethink about development and economic plans in order to improve the living conditions of the population. The main objective of economic diversification agenda is to increase the contribution of these sectors to the gross national product (GDP) of Oman, raise production and create more jobs for these sectors. New technologies will promote the achievement of inclusive, sustainable industrial development through its creation and absorption. New innovations allow businesses to bring new products into the market and improve production efficiency. In addition, industrial development generates new employment and profit incentives. More products and productivity of production also add to the growth of the economy. Industrial development at the same time leads to the manufacture and diffusion of emerging technology. Only by industrialization can economies, industries and businesses build and maintain the requisite technical transition capabilities. This paper presents a conceptual or research framework that identifies the mediating effect of industrial development in the relationship between economic diversification and economic growth in Oman. Two main factors are considered, i.e., the strategic drivers consisting of economic and non-economic variables, and industrial development initiatives. The paper concludes with the discussion on the formulations of hypothesis statements that describe the inter-relationships between the constructs in the conceptual framework. It is expected that the proposed framework can be further verified and tested by using empirical research work.